Multilingual Sydney - Gorfinkel, L.; Gong, Qian (Routledge, 2018)
In this book the authors take an innovative approach that builds on previously published work in two ways. First, it focuses on a single city and, second, it adopts a multidisciplinary approach to multilingualism.